2014
DOI: 10.1016/j.bbamem.2014.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of reversible membrane destabilisation induced by antimicrobial peptides derived from Australian frogs

Abstract: The membrane destabilising properties of the antimicrobial peptides (AMP) aurein 1.2, citropin 1.1, maculatin 1.1 and caerin 1.1, have been studied by dual polarisation interferometry (DPI). The overall process of peptide induced membrane destabilisation was examined by the changes in bilayer order as a function of membrane-bound peptide mass per unit area and revealed three different modes of action. Aurein 1.2 was the only peptide that significantly destabilised the neutral membrane (DMPC), while all four pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Antimicrobial peptides that are known to induce membrane disruption act on the inner/cytoplasmic membrane, which is known to contain disulfide bond-reducing proteins and have a redox potential that favors disulfide bond disruption (Eser et al, 2009;Kadokura et al, 2003). Furthermore, the bacterial membrane is highly fluid and dynamic, and the lytic action of some AMPs has been shown to be reversible (Gee et al, 2013;Hall et al, 2014;Lee et al, 2014). Thus the decline in activity from that measured by flow cytometry (MPC) and that measured by the growth assays (MIC and MBC) is probably due to two factors: the fluid/dynamic nature and disulfide bond-reducing environment of the inner membrane.…”
Section: Synthesis Of Chex-arg20 Multimer Analogsmentioning
confidence: 98%
“…Antimicrobial peptides that are known to induce membrane disruption act on the inner/cytoplasmic membrane, which is known to contain disulfide bond-reducing proteins and have a redox potential that favors disulfide bond disruption (Eser et al, 2009;Kadokura et al, 2003). Furthermore, the bacterial membrane is highly fluid and dynamic, and the lytic action of some AMPs has been shown to be reversible (Gee et al, 2013;Hall et al, 2014;Lee et al, 2014). Thus the decline in activity from that measured by flow cytometry (MPC) and that measured by the growth assays (MIC and MBC) is probably due to two factors: the fluid/dynamic nature and disulfide bond-reducing environment of the inner membrane.…”
Section: Synthesis Of Chex-arg20 Multimer Analogsmentioning
confidence: 98%
“…We have used a range of techniques to determine the mode of action, such as solid‐state NMR, circular dichroism (CD), calorimetry, monolayer studies, surface plasmon resonance, dual polarization interferometry, quartz crystal microbalance, neutron reflectometry and molecular dynamics (MD) simulations. In general, the longer peptides form transmembrane or toroidal pores while the shorter peptides act by a “carpet” or surface mechanism . However, the mechanism (Figure ) depends on the type of lipid and peptide concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The changes in membrane order as a result of AT 1 R-H8 binding were quantitatively examined through the measurement of the changes in optical birefringence (∆ n f ) of the bilayer simultaneously with the membrane-bound peptide mass ( m p ) in real time as previously described2627282930. In particular, the effect of lipid composition on the binding of AT 1 R-H8 to the membrane mimics (DMPC, DMPC/DMPS (80:20), DMPC/DMPS/PI(4)P(76:20:4) and DMPC/DMPS/PI(4,5)P 2 (76:20:4)) was analysed by DPI.…”
Section: Resultsmentioning
confidence: 99%
“…In this study we used DPI to analyze the binding of the binding of AT 1 R-H8 to various bilayer types, some of which include PIPs. DPI is an optical biosensor technology which not only provides information on binding interactions but also allows the measurement of changes in membrane structure in terms of thickness and bilayer order2627282932. We have also previously demonstrated that changes in membrane structure by antimicrobial peptides observed with DPI correlate well with solid state NMR33, and also neutron reflectometry34.…”
Section: Discussionmentioning
confidence: 95%